Biopharmaceutical manufacturing. - Niazi, Sarfaraz, 1949-; Lokesh, Sunitha (IOP (Series). Release 21., 2021)
This two-volume set provides a comprehensive guide to the essential aspects of commercial biopharmaceutical manufacturing. Covering the planning, layout and operation of successful commercial manufacturing, the aim of the books is to enable innovations, new drug development, and make affordable biological drugs available to patients worldwide.